Delayed Hemothorax Due to Thoracic Trauma with Multiple Rib Fracture: A Case Report - Wibowo, Amaro Yudho; Palupi, Sofian; Triyono, Raden Sri (Syntax Corporation Indonesia, 2024)
Recent evidence indicates that elderly who have suffered rib fractures may develop delayed massive hemothorax. Delayed enormous hemothorax after thoracic trauma is uncommon, but it is nevertheless linked to high rates of mortality. This single case report provides an overview of the ordinary and important delayed hemothorax caused by thoracic trauma with multiple rib fractures in limited healthcare facilities. We observe symptoms and chest X-rays before and after the development of delayed hemothorax. A 56-year-old man came to the hospital with complaints of shortness of breath and pain in the chest and right shoulder. The patient said that four days ago, He fell from a height of around 6 meters. After visiting the hospital four days prior, the patient was diagnosed with multiple fractures of the inferior aspect of the right ribs (costa 3-7) as well as a fracture of the right clavicle. However, the patient declined surgery and was made to return home. At that time, the patient did not experience shortness of breath. Currently, the patient is experiencing dyspnea. Blood pressure 138/91 mmHg, heart rate 89 beats per minute, respiration rate 26 times per minute, Spo2 91% room air. The chest x-ray currently shows a right hemothorax. After stabilization, the patient asked to be referred to another hospital for further treatment. Patients with multiple fractured ribs, especially with rib displacement, are at high risk of evolving delayed hemothorax. Close monitoring and observation for several days are necessary.